Tinjauan Tanah Terlantar dalam Perspektif Hukum Islam - Ria Fitri (Universitas Syiah Kuala, 2011)
ABSTRACT: The land is limited source but he need for it to development increase; hence the land should be used efficiently and optimally and make it sustainable. It is in accordance with Article 10 and 15 of the Act Number 5, 1960. Ironically, there is a lot of land left unattended. Solving such land, it is strongly relating to the existing laws. The promulgation of Government Regulation Number 36, 1998 regarding the Use and Managing of Unattended Land, has not been able to handle the problem of unattended land. Based on, Article 5 of the Act Number 5, 1960 regarding Agrarian Law referring to Customary Law that has to respect the elements based on religious values. Islamic law regulates such land. Therefore, this article explores how the definition of such land based on Islamic law. The Overview on Unattended Land in Islamic Law Perspective